The Role of Herbal Medicine as An Alternative Treatment Option for Endometriosis: A Literature Review - Sutrisno, Sutrisno; Paramadina, Putri Nadia (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Endometriosis is a benign gynecological disorder characterized by ectopic growth of endometrial tissue. This condition may deteriorate patient’s quality of life due to pain as its main manifestation and its complications, including impaired fertility and risk of ovarian cancer. Current standard endometriosis treatment still yields numerous side effects and controversy. Thus, herbal medicine is hoped to be the safer alternative treatment with excellent efficacy for endometriosis. Methods: The search of literature published in English or Bahasa Indonesia was performed by incorporating the search queries “endometriosis”, “herbal therapy”, “silymarin”, “curcumin”, “Viburnum opulus”, “Pueraria”, “Allium sativum”, “black garlic”, “naringenin” on databases including PubMed, Cochrane, Springer, Science Direct, Nature, and Google Scholar. The studies included were in vitro studies, in vivo studies, and clinical trials. Results: Various herbal treatments have been widely studied regarding their anti-inflammatory, antioxidant, neuroprotective, hepatoprotective, cardioprotective, antiallergy, and immunomodulatory capacity. A lot of herbal compounds have the potential to suppress and manage endometriosis through various mechanisms, such as inhibiting the migration and adhesion of endometriosis to other tissues, suppressing inflammatory response in endometriosis pathogenesis, generating antioxidant, inhibiting estrogen activity, and inducing apoptosis of endometriosis cell through a number of signaling pathways. Conclusion: Herbal medicine has the potential to manage endometriosis through various mechanisms. Further research is needed regarding the efficacy of herbal therapy in managing endometriosis.